Roland Barthes Semiotic Approach to the Gebyok Jumpara Cultural Video Campaign - Deny Tri Ardiyanto; Andreas Slamet Widodo; Kinanti Erste Panggayuh Putri (Faculty Of Arts and Design Sebelas Maret University, 2023)
The video campaign entitled Gebyok Jumpara is a short-duration cinematic video which is one of the cultural promotional content of Jepara Regency on the Youtube social media platform. Gebyok Jumpara is used to introduce the art of Gebyok carving as a representative carving product that has a close relationship with socio-cultural values in Jepara. This research aims to dissect the content of the Gebyok Jumpara video with the Roland Barthes approach so that the explicit and implicit messages in the video can be revealed more deeply. Based on these objectives, this research emphasizes descriptive qualitative methods to obtain in-depth and accurate findings. Data were collected through observation, interview, and document study. The theoretical approach used is Roland Barthes' semiotic theory with the division of signifier (denotation), signified (connotation), and signification (myth) levels. The initial stage of analysis is the description of the cinematographic composition used in the Gebyok Jumpara video campaign. The next stage is a semiotic analysis using Roland Barthes' theory. The Gebyok Jumpara video campaign will be separated into a total of 9 scenes according to the frame transition. Each scene will be analyzed to classify the level of signs that are translated into the meaning of signifier (denotation), signified (connotation), and signification (myth). The conclusion shows that the Gebyok Jumpara cultural campaign video pays attention to the composition elements of cinematographic techniques such as the role of third, negative space, and natural frame. Meanwhile, the results of the interpretation of meaning through the Roland Barthes approach bring three main messages: the great cultural heritage, the relationship between humans and God as the Greatest Creator, and the acculturation of Hindu, Chinese, and Islamic cultures. These three important points boil down to a message about how humans behave while maintaining tolerance for each other.